1995
DOI: 10.1111/j.1468-0092.1995.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Rome and the East. Production of Roman Provincial Silver Coinage for Caesarea in Cappadocia Under Vespasian, Ad 69–79

Abstract: During the first three centuries AD several eastern provinces of the Roman empire produced silver coinages of specijically local denominations and types. It has been claimed that at certain periods the mint of Rome was employed to strike some of these coinages, rather than the provincial mints to which the coins are traditionally attributed. This claim is based mainly on stylistic observations, but because style is regarded as subjective, some other form of evidence to support these observations is desirable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Another possibility is that we are witnessing a single mint, with blanks being produced in two different places. This suggestion is perhaps less improbable than it might seem: our previous work (Butcher and Ponting 1995) has demonstrated that what appears to be a single silver coinage (in this case provincial issues of Vespasian for Caesarea in Cappadocia) could be produced at two separate mints; the production of blanks in two separate places for a single mint would simply be a variation on this scheme. There are other examples from the Roman world of parts for products being produced in different places to those where they were completed (e.g.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Another possibility is that we are witnessing a single mint, with blanks being produced in two different places. This suggestion is perhaps less improbable than it might seem: our previous work (Butcher and Ponting 1995) has demonstrated that what appears to be a single silver coinage (in this case provincial issues of Vespasian for Caesarea in Cappadocia) could be produced at two separate mints; the production of blanks in two separate places for a single mint would simply be a variation on this scheme. There are other examples from the Roman world of parts for products being produced in different places to those where they were completed (e.g.…”
Section: Resultsmentioning
confidence: 98%
“…It therefore seems clear that the silver content of Nero's post‐64 denarii is 80% across most of the issues defined by Mac Dowall, considerably lower than Walker's figure of 93%. This is the silver standard of 1 part copper to 4 parts silver that we find employed later, under Vespasian and Trajan (Butcher and Ponting 1995; 1998). The only exception seems to be the very last issue, 3b; the two examples of this group that were analysed both had silver bullion contents of about 90% (88.2% and 89.1% respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth is also reduced during this process, but it is accepted that its concentration in metallic silver reflects to some extent to that of the parent ore. The cupellation process, on the other hand, does not affect the gold concentration . Bismuth and gold appear to be then the most important elements related with the original type of the ore, although repeated recycling will gradually homogenize any groupings that may have once existed.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, the ore would be smelted to produce Ag‐rich lead, followed by oxidation to remove most of the lead (as lead oxide) concentrating of the silver in the remaining lead. The silver would be then extracted in small vessels (cupeles) containing bone ash . In this process, most of the remaining lead was removed, but some would inevitably remain, and can be used as an indication of the effectiveness of the procedure.…”
Section: Resultsmentioning
confidence: 99%